An alternate sleeve design in transtibial prosthetics. (2021) - Vignesh, S.; Ramamoorthi, R.; Aravindkumar, N.
Abstract: The term prosthesis is usually used in analogy with Biomechanics. The motion of the body is provided by the bones, joints that form the basic linkage mechanism along with the activity of the muscle. The prime motive of biomechanics is to study about these linkages, their ranges of motion and their degree of freedom. In medicine, a body part which is missing, is been replaced by an artificial device or an extension, namely prosthesis. It is a part of Biomechanics, which deals with the usage of mechanical devices to assist human muscle, skeleton and nervous system in enhancing motor control lost due to trauma, defect or a disease. This paper aims to provide an improved system for lower limb prosthetic users through a better sleeve design. Braided designs with variations are created and analysed. The results suggest that the braided pattern shall be implemented in sleeve design with slight modifications.